2005
DOI: 10.1128/jb.187.6.1892-1900.2005
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Novel Mycobacterium tuberculosis and Mycobacterium smegmatis Mutants Hypersusceptible to β-Lactam Antibiotics

Abstract: Our laboratory previously constructed mutants of Mycobacterium tuberculosis and Mycobacterium smegmatis with deletions in the genes for their major ␤-lactamases, BlaC and BlaS, respectively, and showed that the mutants have increased susceptibilities to most ␤-lactam antibiotics, particularly the penicillins. However, there is still a basal level of resistance in the mutants to certain penicillins, and the susceptibilities of the mutants to some cephalosporin-based ␤-lactams are essentially the same as those o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 45 publications
1
58
1
1
Order By: Relevance
“…Interestingly, M. smegmatis expA mutants showed increased susceptibility to lysozyme and displayed elongated cell morphology with swollen termini. The authors speculated that expA and expB (the Rv2223c homolog) might be directly involved in hydrolytic breakdown of cell wall components or indirectly involved by regulating proteins involved in autolysis or cell wall remodeling (24). Rv2224c is classified as an ␣/␤ hydrolase in a family with both esterase and amidase members (25).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, M. smegmatis expA mutants showed increased susceptibility to lysozyme and displayed elongated cell morphology with swollen termini. The authors speculated that expA and expB (the Rv2223c homolog) might be directly involved in hydrolytic breakdown of cell wall components or indirectly involved by regulating proteins involved in autolysis or cell wall remodeling (24). Rv2224c is classified as an ␣/␤ hydrolase in a family with both esterase and amidase members (25).…”
Section: Discussionmentioning
confidence: 99%
“…pbpX encodes a ␤-lactamase domain; however, it has been reported that in Mycobacterium smegmatis, PbpX does not contribute to ␤-lactam antibiotic resistance. Rather, it was proposed to function as a D,D-carboxypeptidase; however, this has never been confirmed biochemically (38). DegU is an orphan response regulator that regulates flagellar and chemotaxis genes in L. monocytogenes and is severely attenuated during the infection of mice (39)(40)(41)(42)(43).…”
Section: Resultsmentioning
confidence: 99%
“…A mycobacterial AmpG homologue has not yet been identified and characterized, but some transport of the PG material back into the cytosol would be needed. It should be noted that mycobacteria do have ␤-lactamases, enzymes associated with cell wall monitoring and remodeling (136,137,271,434).…”
Section: Do Mycobacteria Recycle Cell Wall Material?mentioning
confidence: 99%